Memorial days : [a memoir] [large type] - Brooks, Geraldine (Random House Large Print Publishing, 2025)
"Many cultural and religious traditions expect those who are grieving to step away from the world. In contemporary life, we are more often met with red tape and to-do lists. This is exactly what happened to Geraldine Brooks when her partner of more than three decades, Tony Horwitz ... collapsed and died on a Washington, D. C. sidewalk.... The demands were immediate and many. Without space to grieve, the sudden loss became a yawning gulf. Three years later, she booked a flight to a remote island off the coast of Australia with the intention of finally giving herself the time to mourn. In a shack on a pristine, rugged coast she often went days without seeing another person. There, she pondered the varied ways those of other cultures grieve, such as the people of Australia's First Nations, the Balinese, and the Iranian Shiites, and what rituals of her own might help to rebuild a life around the void of Tony's death"--